Efforts to Prevent Transnational Crime of Narcotics Smuggling in the Riau Islands Province (Case Study at the Riau Islands National Narcotics Agency) - Putri, Alya Septi Dwirianti; Zulherawan, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Narcotics smuggling as a form of transnational crime poses a serious threat in border regions, particularly in the Riau Islands Province, which has a strategic position and high geographical vulnerability. This study aims to analyze the prevention efforts carried out by the National Narcotics Agency of the Riau Islands Province. The research employs a descriptive qualitative method with a case study approach, using in-depth interviews, observation, and documentation, analyzed through an interactive model. The findings indicate that prevention is implemented through primary, secondary, and tertiary strategies supported by inter-agency collaboration and community participation. This study contributes to strengthening community-based prevention approaches and cross-border cooperation. In conclusion, the effectiveness of prevention is influenced by geographical, social, and institutional factors, highlighting the need for strengthening resources and further longitudinal-based research.Â